2013
DOI: 10.1590/s0102-09352013000600013
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos da parede de levedura em dieta úmida na microbiota fecal, na produção de gás e na morfologia intestinal de gatos adultos

Abstract:  RESUMOO objetivo deste estudo é avaliar os efeitos do extrato de levedura (EPL) em dietas úmidas sobre a microbiota fecal, a produção de gás e a morfologia intestinal de gatos adultos. Foram utilizados 20 gatos adultos, de ambos os sexos, distribuídos ao acaso em quatro tratamentos: 1) dieta comercial úmida (controle); 2) controle + 0,2% de extrato de levedura em matéria seca; 3) controle + 0,4%; e 4) controle + 0,6%. Foram realizadas a microbiologia fecal, a avaliação da morfologia intestinal por meio de ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 14 publications
0
4
1
Order By: Relevance
“…In the context of this study, it was observed that there was mod- , GOS and YCW); in those studies, the authors did not find a reduction in potentially pathogenic bacteria (Aquino et al, 2013;Kanakupt et al, 2011;Strickling et al, 2000;Swanson, Grieshop, Flickinger, Bauer, Healy, et al, 2002).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In the context of this study, it was observed that there was mod- , GOS and YCW); in those studies, the authors did not find a reduction in potentially pathogenic bacteria (Aquino et al, 2013;Kanakupt et al, 2011;Strickling et al, 2000;Swanson, Grieshop, Flickinger, Bauer, Healy, et al, 2002).…”
Section: Discussionmentioning
confidence: 51%
“…Barry et al., found a reduction in E. coli in cat feed supplemented with 4% FOS. However, these findings are in contrast with studies conducted in dogs and cats fed different prebiotics (FOS, MOS, xylo‐oligosaccharides [XOS], GOS and YCW); in those studies, the authors did not find a reduction in potentially pathogenic bacteria (Aquino et al., ; Kanakupt et al., ; Middelbos, Fastinger, & Fahey, ; Strickling et al., ; Swanson, Grieshop, Flickinger, Bauer, Healy, et al, ).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Supplementation with a microencapsulation of probiotic strains which include S. cerevisiae for 20 days resulted in fecal Lactobacillus count increase, but the effect of yeast cannot be isolated in this study (113). Aquino et al (110) did not find differences in lactic acid bacteria counts nor clostridium-reductor when substituting up to 0.6% of the wet diet with yeast extract in cats. There were no differences in cats' fecal pH when SCFP or yeast extract was supplemented (107, 109).…”
Section: Ycwcontrasting
confidence: 52%
“…In addition some authors (Freimund et al 2005;Pinto et al 2015) reported that the chemical composition of the yeast cell walls, in terms of ether extract, crude protein and crude fibre, is highly affected by the starting materials but also by the production process. The differences in nutrient composition noticeably affect the functional effect when cat diets are supplemented with yeast cell wall (Aquino et al 2013;Santos et al 2018). As a consequence, it is quite difficult to predict the real effects of a new functional product and to compare the results of different studies using supplementations based on yeast cell wall, because their availability and fermentability in the large intestine could differ a lot.…”
Section: Discussionmentioning
confidence: 99%